IMPLEMENTASI PERIZINAN IMPOR BAWANG PUTIH (STUDI KASUS DISTRIBUTOR BAWANG PUTIH CV NIKO ESTER) - Mutia Islamiati Mulyadi Mutia Islamiati Mulyadi; Achsanul Nashir Achsanul Nashir (JAMBIS : Jurnal Administrasi Bisnis, 2022)
Fulfillment of the need for garlic in Indonesia from year to year continues to increase. Both in terms of market demand and very limited availability in the country, meeting the needs of this commodity has made Indonesia-China cooperation relations even closer in the trade sector.In 2020, the need for consumption of garlic reaches 424 thousand tons while the production of garlic is only 100 thousand tons. So that Indonesia is really needed to import garlic. In importing garlic, business actors must have certain conditions to obtain an import permit and currently there is a new regulation in import licensing, namely using the INSW (Indonesia National Single Window) system. The INSW (Indonesian National Single Window) system has the goal of creating integrated data between ministries and agencies, and becoming a superset of data to eliminate repetition and duplication. However, business actors are still not used to using the INSW (Indonesia National Single Window) system.This study aims to analyze the implementation of garlic import licensing. The type used is descriptive qualitative research. The results show that there are three theoretical concepts of absolute advantage in the implementation of import licensing in meeting consumption needs, namely: 1. Division of Labor in producing goods is able to reduce operational costs so as to increase profits on sales of products, 2. Specialization and Product Efficiency, Absolute advantage can only happen if a country can produce goods and services in accordance with the resources owned by the region.